Oral-cavity platform for monitoring physiological signs during physically demanding activities - de Almeida e Bueno, L (2023)
The focus of this research is the development of a platform to measure physiological signals in the oral cavity during real-world conditions. Starting from a literature review the current state-of-the-art for oral-cavity sensors was determined. No existing measurement system that could capture all relevant physiological data during physically demanding activities was found. A novel wearable oral-cavity measurement system was proposed to address this.